An updated review of the epidemiological factors associated with recurrent respiratory papillomatosis. Issue 2 (28th January 2021) - Welschmeyer, Alexandra; Berke, Gerald S.
Abstract: Objectives: To identify studies evaluating the epidemiology of recurrent respiratory papillomatosis (RRP), including patient demographics, human papillomavirus (HPV) immunology, clinical course, surgical and medical treatments, and psychosocial factors. Methods: A systematic literature search through PubMed was performed to identify studies evaluating the epidemiological factors associated with RRP. All studies were screened through a priori selection criteria using the titles and abstracts. Results: A total of 208 studies were identified, of which 54 met eligibility criteria and were included in the review. Conclusions: RRP is a rare disease most commonly caused by HPV 6 and 11. It is characterized by recurring benign papillomatous lesions in the respiratory tract, particularly the larynx. Existing evidence about disease risk factors is limited but includes both maternal HPV infection and patient smoking and sexual behaviors. Disease management involves a combination of routine surgical and medical treatment. Surgical techniques include CO2 ‐laser, sharp dissection, coblation, microdebridement, and photoangiolytic laser. Medical treatments which have been found to facilitate disease control off‐label include interferon‐alpha (IFN‐α), indole‐3‐carbinol, acyclovir, bevacizumab, retinoids, and the Gardasil and mumps vaccines. Many patients suffer from additional psychosocial challenges related to their diagnosis. Current disease knowledge remains limited, and more robust controlled trials about risk factors, medical therapies, and surgical options are needed. Level of Evidence: 5. Abstract : Recurrent respiratory papillomatosis (RRP) is a rare disease caused by human papillomavirus (HPV) characterized by recurring benign papillomatous lesions in the respiratory tract and are often refractory to treatment. The aim of this review is to identify studies evaluating the epidemiology of recurrent respiratory papillomatosis, including patient demographics, human papillomavirus immunology, clinical course, surgical and medical treatments, and psychosocial factors.